Neurotechnological Approaches to the Diagnosis and Treatment of Alzheimer’s Disease - Ning, Shen; Jorfi, Mehdi; Patel, Shaun R.; Kim, Doo Yeon; Tanzi, Rudolph E. (Frontiers in Neuroscience, 2022)
Alzheimer’s disease (AD) is the most common cause of dementia in the elderly, clinically defined by a gradual decline in memory and cognitive function and pathologically by brain atrophy, neuroinflammation, and accumulation of extracellular amyloid plaques and intracellular neurofibrillary tangles. Neurotechnological approaches, including optogenetics and deep brain stimulation, have exploded as new tools for not only the study of the brain but also for application in the treatment of neurological diseases. Here, we review the current state of AD therapeutics and recent advancements in both invasive and noninvasive neurotechnologies that can be used to ameliorate AD pathology, including neurostimulation via optogenetics, photobiomodulation, electrical stimulation, ultrasound stimulation, and magnetic neurostimulation, as well as nanotechnologies employing nanovectors, magnetic nanoparticles, and quantum dots. We also discuss the current challenges in developing these neurotechnological tools and the prospects for implementing them in the treatment of AD and other neurodegenerative diseases.